Community Service at Leadership Training II for Naval Polytechnic Cadets, Kindergarten. IV Ta. 2023 “Millennial Leadership in Facing Golden Indonesia 2045” - Teguh Setiawan Wibowo; Ferdy Edwin Takaendengan; Muhammad Syukur (Jurnal Pengabdian Masyarakat Bestari, 2023)
The rise of Indonesia's golden generation (known as the millennial generation) brings great potential for economic growth and national development towards the 100th anniversary of Indonesia's independence in 2045, so it requires leadership education that can become a solid foundation in facing future challenges. The aim of this leadership training activity are improve the quality of the millennial generation of productive age and form future leaders of the Indonesian nation who are wise, efficient, skilled and highly dedicated in realizing the vision of a Golden Indonesia 2045. The methods used are lecture sessions or material presentations, FGDs (discussion between invited participants), discussion session and workshop. The result is the community service through this leadership training activity received quite good response and enthusiasm from the participants. It is hoped that this leadership training activity can be an opportunity to form subsequent collaborative activities with other universities on a larger scale and have a positive impact on national development.